How many plasmids can bacteria carry? A synthetic biology perspective - Cholpisit Kiattisewee (Open Biology, 2025)
Plasmids are pinnacle tools in synthetic biology and other biotechnological applications. They serve as the simplest approach to introduce recombinant DNA, which is then transcribed into RNA that functions as is or is translated into a protein of interest. Despite their widespread utility, the question ‘how many plasmids can be used in this bacterium?’ remains underexplored in the existing literature. In this article, I discuss the maintenance of multiple unique plasmids in bacteria through a microbial synthetic biology perspective, both in theoretical and practical aspects. I delve into the existing evidence of multi-plasmid systems, aiming to pinpoint the possible maximum number of unique plasmids a single microbe can carry. Finally, I highlight how the existing applications of multi-plasmid systems drive novel discovery and development in metabolic engineering, synthetic biology and other relevant areas in comparison to other non-plasmid strategies.